ANALISIS PENGETAHUAN DAN PEMAHAMAN INVESTASI TERHADAP MINAT MAHASISWA PRODI AKUNTANSI DI UNIVERSITAS KOTA BATAM - Sihombing, Veronica Yulianti; Viola Syukrina E Janrosl (LPPM Universitas Putera Batam, 2022)
Interest in investing in students shows an understanding of the knowledge that has been learned. Understanding of investment by students can be seen through the interest in investing which is increasingly marketed from time to time. One way to determine student interest in investing is by analyzing investment knowledge and understanding. This research was conducted to determine the effect of investment knowledge and understanding on student interest in investing. The independent variable in this study is knowledge and understanding of investment. The independent variable in this study is student interest. The results showed that the investment knowledge variable had no effect on student interest. Investment understanding has an effect on student interest. The results of the F test show that investment knowledge and understanding of investment simultaneously affect student interest. The value of Adjusted R Square shows that together knowledge and understanding of investment contribute to student interest by 22.4% while the remaining 77.6% is influenced by other variables not included in this study.